Creative Thinking Ability of Mathematics Students in Solving Geometry Problems Viewed of Adversity Quotient - Ikha Yuliati; Dwi Juniati; Siti Khabibah (Universitas Teknokrat Indonesia, 2025)
This study examines the creative thinking abilities of mathematics student teachers in solving geometry problems, analyzed through the lens of Adversity Quotient (AQ). The participants, categorized as climbers, campers, and quitters, displayed varying levels of creative thinking based on three indicators: fluency, flexibility, and novelty. Climber students achieved fluency and flexibility by producing multiple logos using two different methods but lacked novelty as their approaches relied on existing methods. Campers demonstrated flexibility by using two distinct approaches but failed to meet fluency and novelty criteria. Quitters only met the fluency indicator and were at the less creative level. None of the subjects fulfilled the originality indicator, highlighting a critical gap in creative thinking skills among the participants. These findings underline the importance of fostering creative thinking in mathematics education, especially for student teachers who will later nurture such skills in their students. Enhancing the quality of mathematics instruction by incorporating open-ended problems and promoting a culture of mathematical thinking is essential. This aligns with the educational aim to balance analytical and creative thinking as fundamental aspects of problem-solving in mathematics.